2010
DOI: 10.5812/asjsm.34858
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise on Memory Consolidation and Retrieval of Passive Avoidance Learning In Young Male Rats

Abstract: Purpose: Previous studies have shown that physical activity improves learning and memory. Present study was performed to determine the effects of short term and long term treadmill exercise on learning, memory consolidation and retrieval of passive avoidance learning in an animal model. Methods:In this study fifty male Wistar rats with 3-4 months of age were randomly divided into five groups (n=10 in each group). Control group was trained in passive avoidance box and was tested 10 min, 24 hr, 10 days and 3 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Although some evidences have indicated the significant promotion of cognitive performance, learning and memory by physical activities (Ang and Gomez-Pinilla, 2007;Cotman and Berchtold, 2002;García-Capdevila et al, 2009;Leasure and Jones, 2008;Lin et al, 2012;Saadati et al, 2010;Van Praag et al, 1999) other studies, in agreement with our findings, have revealed lack of improvement (Titterness et al, 2011;Zagaar et al, 2012a,b). This controversy OVX (ovariectomized) (B) female rats.…”
Section: Discussionsupporting
confidence: 93%
“…Although some evidences have indicated the significant promotion of cognitive performance, learning and memory by physical activities (Ang and Gomez-Pinilla, 2007;Cotman and Berchtold, 2002;García-Capdevila et al, 2009;Leasure and Jones, 2008;Lin et al, 2012;Saadati et al, 2010;Van Praag et al, 1999) other studies, in agreement with our findings, have revealed lack of improvement (Titterness et al, 2011;Zagaar et al, 2012a,b). This controversy OVX (ovariectomized) (B) female rats.…”
Section: Discussionsupporting
confidence: 93%
“…Treadmill exercise improved spatial learning memory [ 49 , 50 ]. A study investigating the effect of exercise on different stages of memory revealed that treadmill running improved the consolidation of passive avoidance memory but had no effect on memory retrieval [ 51 ]. Moreover, physical exercise improved cognitive performance in psychogeriatric patients [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This test is performed 24 hours after the acquisition phase. In a study by Saadati et al (39), cognitive function was measured by avoidance learning, and it was found that the difference between test types may lead to different results in evaluation exercise effects on memory.…”
Section: Discussionmentioning
confidence: 99%